(3EQTGO GdbGUO Edi CSfi GdebGUOs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3hHYO , aEf HfG MGLI Edi Jcejd fahSfG GdHTQjI ai bhGgG GdfXQjI s
(3BNQgG (B:s
(3hgPg GdebhdGJ TGedI dLejY GdehLhOGJ GdeecfI hdjcf gPG BNQ GdcdGe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs